Perilaku Adsorpsi Emas Dari Larutan Ammonium Thiosulfat Dengan Karbon Aktif Dan Resin Penukar Ion [Study of Adsorption Behaviour of Gold from Thiosulfate Solution onto Activated Carbon and Ion Exchange Resin] - M, Wahyudin Prawira; Mubarok, M Zaki (Metalurgi, 2016)
Effective recovery methods of gold from thiosulfate solution are still being studied by many researchers. In this paper, results of gold adsorption tests in ammonium thiosulfate solutions using 3 types of ion exchange resin and activated carbon is discussed. Series of batch adsorpsion tests at room temperature have been carried out within pH range of 7-9 to study Au adsorption behaviour from thiosulfate solution onto four types of adsorbents, loading capacity and adsorption kinetics of each adsorbent. The investigation results show that recovery of gold from pregnant leach solution of gold ore in ammonium thiousulfate can be effectively performed by using a strong-base resin of Lewatit Monoplus MP 800. At a pH range of 7-9, adsorption percentages of Au onto the strong-base resin of Lewatit Monoplus MP exceed 97% after 2 hour and reach a maximum level of 100% after 25 hour at pH 8. In contrast, activated carbon did not exhibit a sufficient performance in recovery of Au from thiosulfate solution, in which the highest adsorption percentage of Au after 25h <80% at pH range of 7-9. The strong base resin of Lewatit Monoplus MP 800 demonstrated the highest loading capacity and fastest adsorption rate followed by weak base resin of Guanidine, polymeric resin with carbon matrix AF5 and activated carbon at pH range of 7-9.AbstrakTeknik perolehan kembali emas yang efektif dari larutan thiosulfat masih terus dipelajari oleh para peneliti. Pada penelitian ini dibahas hasil-hasil percobaan adsorpsi emas dalam larutan ammonium thiosulfat dengan menggunakan 3 tipe resin penukar ion dan karbon aktif. Serangkaian percobaan adsorpsi batch pada suhu kamar dilakukan dalam selang pH 7-9 untuk mempelajari perilaku adsorpsi Au dari larutan thiosulfat pada keempat jenis adsorben, kapasitas adsorpsi dan laju adsorpsi Au pada masing-masing adsorben. Hasil percobaan menunjukkan bahwa perolehan emas dari larutan hasil pelindian bijih emas dalam larutan ammonium thiosulfat dapat dilakukan dengan efektif menggunakan resin penukar ion tipe basa kuat Lewatit Monoplus MP 800. Dalam rentang pH 7-9, persen adsorpsi Au pada resin basa kuat Lewatit Monoplus MP800 melebihi 97% setelah 2 jam dan mencapai level maksimum 100% setelah 25 jam pada pH 8. Sebaliknya, karbon aktif tidak menunjukkan performa yang memadai untuk mengambil kembali Au dari larutan thiosulfat pada mana persen adsorpsi Au tertinggi setelah 25 jam kurang dari 80% dalam rentang pH 7-9. Resin basa kuat Lewatit Monoplus MP 800 menunjukkan kapasitas adsorpsi Au paling tinggi dan laju adsorpsi paling cepat diikuti oleh resin basa lemah Guanidine, resin polimerik bermatriks karbon AF5 dan karbon aktif dalam rentang pH 7-9.